Emergence of dengue virus type 4 during COVID-19 pandemic in patients admitted to a teaching hospital in Malaysia - Mahrunissa Mahadi,; Siti Norlia Othman,; Najma Kori,; Sharifah Azura Salleh,; Zetti Zainol Rashid,; Petrick Periyasamy,; Nor Azila Muhammad Azami,; Noraidatulakma Abdullah,; Hui-min Neoh, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Prior to COVID-19, dengue was an important public health problem in Malaysia. Due to the movement control order imposed by the Malaysian government to curb the COVID-19 transmission, a study predicted that mosquito-borne diseases would increase during lockdown and partial lockdown seasons. Thus, this study aims to determine the current situation of dengue incidence during the pre-COVID-19 pandemic (2019) and during the COVID-19 pandemic (2020 and 2021). We compared the number of laboratory-confirmed cases in the pre-COVID19 year (2019) and during the COVID-19 pandemic (2020 and 2021). In addition to that, we characterized the clinical manifestation, dengue serotype and viremia levels of dengue patients that were admitted to the Hospital Cancelor Tuanku Muhriz. We found a significant decrease in the number of laboratory-confirmed cases between COVID-19 pandemic and the pre-covid period (p2020=0.064; p2021<0.001). In this study, we found DENV 4 serotype was the most common serotype in dengue patients admitted to our hospital. There was no significant correlation between DENV serotype/viremia level with clinical manifestation of dengue fever and dengue with warning signs. However, patients infected with DENV4 had the highest viral load compared to patients infected with other serotypes. We also found high viremia levels were significantly associated with the febrile phase.